Pengaruh Promosi, Harga, dan Citra Merek Terhadap Keputusan Pembelian Sepeda Motor Yamaha di DKI Jakarta - Quranis Siva, Dahliana; Abdullah , Zed (SM Institute, 2025)
ABSTRACT This research aims to analyze the influence of promotion, price and brand image on purchasing decisions for Yamaha motorbikes in DKI Jakarta. This research uses a quantitative method with a positivism approach which considers reality as something single and can be measured with valid and reliable instruments. Data was collected through a questionnaire distributed to respondents who were Yamaha motorbike consumers in DKI Jakarta. The research results show that partially, promotions have a significant negative effect on purchasing decisions for Yamaha motorbikes in DKI Jakarta. The t-statistic value for the influence of promotions on purchasing decisions is -2.053 with a p-value of 0.020, which means the hypothesis is accepted. Price also has a significant influence on purchasing decisions. The t-statistical value for the influence of price on purchasing decisions is 2.237 with a p-value of 0.013, so the hypothesis is accepted. Brand image has the strongest influence on purchasing decisions with a t-statistic value of 6.596 and a p-value of 0.000, which shows that this hypothesis is very significant. Keywords : Promotion; Price; Brand Image; Purchase Decision